Battery Materials Technology Trends and Market Drivers for Automotive Applications : Challenges for science and industry in electric vehicles growth. Issue 3 (1st July 2020) - Ball, Sarah; Clark, Joanna; Cookson, James
With the electric vehicle (EV) market set to grow rapidly over the coming years, the industry faces a challenging ramp-up of volume and material performance demands. From the current trend towards high-energy high-nickel cathode materials, driven in-part by consumer range anxiety, to the emergence of solid-state and beyond lithium-ion technologies, herein we review the changing requirements for active materials in automotive Li-ion battery (LIB) applications, and how science and industry are set to respond.